Religious Moderation as a Bridge to Peace: Fostering Tolerance, Mutual Understanding, and Interfaith Dialogue - Vita Mulyanti; Kurnia Muhajarah (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: Indonesia’s diversity has made it vulnerable to rising extremism and radicalism, prompting the Ministry of Religious Affairs to promote religious moderation as a strategic effort to preserve unity and tolerance. Objective: This study aims to explore the implementation of religious moderation by the Ministry of Religious Affairs as a strategy to combat extremism and radicalism in Indonesia. Method: The research uses a qualitative approach with a literature study method conducted in 2022. Data collection techniques include documentation, and data analysis follows the Miles & Huberman model. Result: The findings indicate that religious moderation acts as a meeting point between religious extremism and the path to peace, providing a solution to reconcile religious communities. It is crucial in fostering peaceful and prosperous life, as well as promoting cultural strategies for building peace in Indonesia. Conclusion: The study concludes that religious moderation is essential for maintaining human dignity and addressing the diverse challenges of modern development. It plays a key role in mitigating radical ideologies and contributing to social harmony in Indonesia. Contribution: This research contributes to the understanding of religious moderation as a strategic tool to counter radicalism, highlighting its role in promoting peace, cultural cohesion, and human dignity in a diverse society. It offers insights for policymakers and religious leaders in fostering moderation in the face of modern challenges.